Smart health monitoring system utilizing Internet of Things (IoT) and Arduino - Mohd Saad, Norhashimah; Mihat, Ameyshafida; Shair, Ezreen Farina; Abdul Rahim, Rohana; Nasir Aslam, Achmad Bayhaqi (AJMedTech, 2022)
The use of healthcare monitoring systems in hospitals and other health facilities has grown exponentially, and portable healthcare monitoring systems based on new technologies have emerged as a severe concern in several countries throughout the globe. The emergence of the Internet of Things (IoT) technology has contributed to the progress of healthcare from face-to-face counseling to telemedicine. The project aims to design a reliable health monitoring system utilizing the IoT, Arduino,and Android applications. It can be used to measure body temperature, heart rate,and level of oxygen in the blood in both hospitals and homes. The system is also capable to verify that the transmission of the sensor’s data to the host computer is done in real-time.The results show that the system reading is approximately 100% accurate as of the purchased measuring instruments or actual devices. Therefore, doctors and family members can now monitor and track the patient’s health anywhere through this smart health monitoring system.